PENGARUH MOTIVASI BELAJAR DAN KECERDASAN SPIRITUAL PADA PRESTASI BELAJAR MAHASISWA AKUNTANSI - Ni Putu Trisna Windika Pratiwi (UNHI Press, 2019)
Learning achievement plays an important role in measuring how much understanding an individual gets in the learning process that has been followed. The purpose of this study is to provide empirical evidence regarding the effect of learning motivation and spiritual intelligence on the learning achievements of accounting students at the Faculty of Business Economics and Tourism, Hindu Indonesia University. The sample collection method used is a nonprobability sampling technique with a saturated sampling method, so that the number of samples used in this study were 68 students. Research data was collected through questionnaires and analyzed using multiple linear regression analysis techniques. The test results in this study prove that learning motivation and spiritual intelligence have a positive effect on student learning achievement.